Efektivitas Board Game Ranah Minang sebagai Media Edukasi melalui Focus Group Discussion (FGD) - Mayang Sari, Riska (Jurnal Seni Urban dan Industri Budaya, 2023)
Minangkabau culture is a culture that is owned by the Minangkabau people and develops throughout the Minangkabau area and overseas areas. This culture is one of the two major cultures in the archipelago which are very prominent and influential. Minangkabau culture must continue to be preserved by the Minang community so that it does not fade with the times. In the past, BAM was a subject that had to be in class, especially in West Sumatra. Applied at the elementary level by exploring the original Minangkabau culture. However, along with the times and the change of the Education Unit Level curriculum (KTSP) to the 2013 Curriculum (K13) curriculum, BAM subjects were no longer studied in schools in West Sumatra, especially Padang Pariaman. Departing from this condition, an educational media was created in the form of the Minang Ranah board game which was specifically designed as a strategy to maintain Minangkabau natural culture so that children can still get to know the culture in a fun and not monotonous way. And a study was conducted which aimed to determine the effectiveness of the Minang Ranah Board Game which consisted of board game design, language, material and effective gameplay for the application of the educational board game. The method used in research on the application of board games as a media for Minangkabau culture education is qualitative and Focus Group Discussion (FGD). From the Focus Group Discussion (FGD) that has been conducted, it was found that Minangkabau educational board games are effective as an attraction for children to learn Minangkabau natural culture in terms of material, design and gameplay that make children happy while learning while playing. Budaya Minangkabau adalah kebudayaan yang dimiliki oleh masyarakat Minangkabau dan berkembang di seluruh kawasan dan daerah perantauan Minangkabau. Budaya ini merupakan salah satu dari dua kebudayaan besar di Nusantara yang sangat menonjol dan berpengaruh. Budaya Minangkabau harus terus dilestarikan oleh masyarakat minang agar tidak pudar oleh perkembangan zaman. Dulu BAM ini merupakan mata pelajaran yang harus ada di kelas terutama daerah Sumatera Barat. Diterapkan pada jenjang SD dengan mendalami budaya asli minangkabau. Namun seiring perkembangan zaman sertaÂ  pergantian kurikulum Tingkat Satuan Pendidikan (KTSP ) menjadi kurikulum Kurikulum 2013 (K13) mata pelajaran BAM sudah tidak dipelajari di sekolah-sekolah Sumatera Barat khususnya Padang pariaman. Berangkat dari kondisi ini diciptakan sebuah media edukasi dalam bentuk board game Ranah Minang yang dirancang khusus sebagai strategi mempertahankan budaya alam minangkabau agar anak anak bisa tetap mengenal budaya dengan cara yang menyenangkan dan tidak monoton. Dan dilakukan sebuah penelitian yang bertujuan untuk mengetahui efektifitas dari Board Game Ranah MinangÂ  yang terdiri dari Desain Board game, Bahasa, materi dan alur permainan yang efektif untuk pengaplikasian board game edukasi tersebut. Metode yang digunakan dalam penelitian penerapan board game sebagai media edukasi budaya Minangkabau ini adalah kualitatif dan Focus Group Discussion (FGD). Dari Focus Group Discussion (FGD) yang telah dilakukan ditemukan bahwa board game edukasi Minangkabau efektif sebagai daya Tarik anak-anak untuk belajar budaya alam Minangkabau dari segi materi, desain serta alur permainan yang membuat anak-anak senang saat belajar sambil bermain. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//